PENGGUNAAN FESTO FLUIDSIM SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA DI SMK NEGERI 2 BANDA ACEH - sri wahyuni (PTE FTK UIN Ar-Raniry, 2019)
Festo Fluidsim is a computer-based learning media that can be used to facilitate students inunderstanding learning methods. Festo Fluidsim is an application for making basic electronic circuits,then followed by pneumatic and electro-pneumatic circuits that can be directly simulated. The mediais suitable for use as a learning medium to help improve the learning outcomes of students majoringin industrial electronics engineering who are studying the basic subjects of electricity and electronicsat SMK Negeri 2 Banda Aceh. The type of this research is a quantitative study using the experimentalmethod, forming 2 study groups, control and subsequent experiments conducted data collection withthe test method. The results obtained indicate an increase in the value of learning outcomes from anaverage pretest 46.19 to an average at 88.21 posttest. Similarly, based on the results of statistical testsconducted, obtained an average value of N-Gain 0.79 <0.7 which can be categorized as high, the resultsof the criteria of pretest significance value 0.13> 0.05 and posttest significance value 0.59> 0 , 05which is normally distributed, and subsequently gets a Sig. (2-tailed) score is 0,000 which is smallerthan 0.05, so it can be concluded that the use of Festo Fluidsim as a learning medium can effectivelyimprove student X learning outcomes of Elementary subjects Electricity and Electronics SMK Negeri2 Banda Aceh